Platinum Dissolution and Redeposition from Pt/C Fuel Cell Electrocatalyst at Potential Cycling. Issue 6 (16th March 2018) - Pavlišič, Andraž; Jovanovič, Primož; Šelih, Vid Simon; Šala, Martin; Hodnik, Nejc; Gaberšček, Miran
Abstract : Extremely sensitive on-line detection of metal ions concentration was used to investigate potential-resolved platinum dissolution from commercial fuel cell electrocatalyst. The experiments were carried out in an electrochemical flow cell connected to inductively coupled plasma mass spectrometer. A variety of electrochemical treatments using different voltage scan rates confirmed the previously observed primary platinum degradation mechanism - the so-called "transient dissolution". Importantly, the redeposition of dissolved platinum is now shown to play an important role in the overall effective Pt dissolution. Pt redeposition trends exhibit a significant dependence on voltage scan rate.